Chronic Lymphocytic Leukemia Concomitant with COVID 19: A Case Report - Ali, Elrazi (Am J Case Rep, 2020)
Patient: Male, 49-year-old Final Diagnosis: Chronic lymphocytic leukemia • COVID-19 Symptoms: Feve • shortness of breath Medication: — Clinical Procedure: — Specialty: Hematology • Infectious Diseases OBJECTIVE: Unusual clinical course BACKGROUND: COVID-19 is a newly emerging disease that is not yet fully understood. It is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel virus that is easily transmitted from human to human through the respiratory route. Usually, it presents with fever, headache, fatigue accompanied by respiratory symptoms like cough and dyspnea, and other systemic involvements. Chronic lymphocytic leukemia (CLL) is a common lymphoproliferative neoplasm characterized by absolute lymphocytosis and demonstration of clonality unlike other causes of lymphocytosis. Patients with CLL are considered immunocompromised because of impaired humoral immunity (mainly) and cellular immunity. Therefore, they are vulnerable to various infections including COVID-19. Little is known about the COVID-19 infection when it unmasks CLL. CASE REPORT: A 49-year-old man with no significant previous illnesses, and an unremarkable family history, presented with a moderate COVID-19 infection. He initially presented to the emergency department with fever and mild shortness of breath. A complete blood count showed a high white blood cell count with absolute lymphocytosis. Flow cytometry revealed the clonality of the lymphocytes confirming the diagnosis of CLL. Despite having CLL, he developed a moderate COVID-19 infection and recovered in a few days. To the best of our knowledge, this is the first report of CLL, which presented with a COVID-19 infection as the initial presentation. CONCLUSIONS: Lymphocytosis is an unexpected finding in patients diagnosed with COVID-19 infection and the elevated lymphocytes may be indicative of other conditions. Secondary causes of lymphocytosis like malignancy or other infections should be considered in these cases.